2017
DOI: 10.1007/s12144-017-9768-4
|View full text |Cite
|
Sign up to set email alerts
|

Can you buy work engagement? The relationship between pay, fringe benefits, financial bonuses and work engagement

Abstract: What role do financial rewards play as predictors of work engagement? To address this question, based on the Job DemandsResources Theory (JD-R), the relationship between financial rewards and work engagement on a large sample (N = 1201) of multi-occupational employees was investigated. Through three steps of hierarchical regression, salary, fringe benefits, and bonuses were added to a JD-R model predicting work engagement via job resources and job demands; however, this did not lead to any significant improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 63 publications
2
24
0
2
Order By: Relevance
“…The results of research that prove the Influence of Transformational Leadership on Remuneration are in line with Wiraatmadja et al (2015), Chen et al (2012), and Kulikowski and Piotr (2020). However, Remuneration does not affect Work Engagement, in line with Kulikowski and Piotr (2020), that financial rewards which include salary, allowances, and bonuses cannot increase Work Engagement.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of research that prove the Influence of Transformational Leadership on Remuneration are in line with Wiraatmadja et al (2015), Chen et al (2012), and Kulikowski and Piotr (2020). However, Remuneration does not affect Work Engagement, in line with Kulikowski and Piotr (2020), that financial rewards which include salary, allowances, and bonuses cannot increase Work Engagement.…”
Section: Discussionsupporting
confidence: 83%
“…Park et al (2016), also have the same opinion, that this research was conducted on teachers in Korea using elements of transformational leadership from Bass and Avolio (1994). Kulikowski and Piotr (2020), the relationship between financial rewards and engagement, in the form of salary, additional benefits, and bonuses increases Work Engagement but does not lead to a significant increase in model fit and all new predictors are not significant. Ludviga and Kalvina (2016), the relationship between job satisfaction, Work Engagement, and loyalty as well as the impact of trust and job meaningfulness on Work Engagement and job loyalty.…”
Section: Hypothesis Development Transformational Leadership Style Formentioning
confidence: 87%
“…Due to the COVID-19 pandemic, employees, particularly those engaged in moonlighting (working another job), are generally more aware of the financial security issue. Recent studies on work engagement and job performance have shown that employees ranked financial security as a factor of the highest significance ( Kulikowski and Sedlak, 2020 ). When their employers in mandatory quarantine are unable to provide job protection and income replacement, employees are likely to experience a complicated array of negative emotions and work stress that may impair their work effort and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Although, to the best of our knowledge, little is known about the direct relation between pay level and WE, the contemporary literature allows us to assume that this relation is negligible. For example, Hulkko-Nyman et al (2012) and Kulikowski and Sedlak (2017) have found that pay level was not significantly related to WE, and other studies postulate that it is rather pay perception (e.g. pay satisfaction), not the pay level per se, which influences employee attitudes and behaviors (Currall et al, 2005;Tekleab et al, 2005).…”
mentioning
confidence: 99%